Model Penilaian Portofolio untuk Meningkatkan Kemandirian Peserta Didik: Sebuah Kajian Literatur - Defika Putri Nastiti; Sigit Santoso; Sudiyanto Sudiyanto (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
Currently the world is preparing for the era of society 5.0, in this era the education sector encourages the development of a more personal way of learning, so that students' learning independence and unique approaches to learning are prioritized. Learning independence plays an important role for students, because students are required to be able to take responsibility for making decisions related to their learning process and have the ability to carry out the decisions they make. In fact, the learning independence of students tends to be low, this is due to the learning objectives and non-specific learning methods that lead to increasing learning independence. Teachers must have the will and skills to change the way they relate to students, starting from paying attention to students' initial independence, teaching materials used, learning, scenarios or syntax and learning assessment. The main focus of this study is on the use of the portfolio assessment model as an effort to increase the learning independence of students in learning economics. The results of the study concluded that the use of the portfolio assessment model can increase the learning independence of students. So that the portfolio assessment model needs to be developed to increase the learning independence of students in learning economics